Advancing Organizational Sustainability Through Green Hrm: The Mediating Roles of Green Innovation and Employee Environmental Performance - Kharel, Shreekrishna; Chhetri, Ashmita Dahal; Sharma, Santosh (Journal of Balkumari College, 2025)
This study explores the impact of Green Human Resource Management (GHRM) practices on organizational sustainable performance (OSP), emphasizing the mediating role of green innovation (GI) and employee green performance (EGP). Rooted in the Ability-Motivation-Opportunity (AMO) theory and Social Identity Theory, the research investigates how key GHRM components green recruitment and selection (GRS), green training (GT), and green pay and reward (GPR) influence sustainability outcomes within Nepalese organizations. Drawing data from 200 respondents across diverse industries in Chitwan, Nepal, the study employed a positivist, deductive research approach with a cross-sectional survey design. Data analysis is using SPSS revealed strong positive correlations between GHRM practices and OSP, with EGP emerging as the most significant predictor. Regression analysis confirmed that GPR and GI significantly contribute to OSP, while GT and GRS were found to be statistically insignificant. These findings underscore the importance of behavioral and innovation focused HR strategies in driving sustainability. The study contributes to the evolving discourse on GHRM by contextualizing global frameworks within a developing economy and offers practical implications for HR practitioners and policymakers. Future research is recommended to explore the roles of green transformational leadership, technology integration, and longitudinal effects of GHRM practices on sustainability.